Edukasi Pencegahan Penyakit Paru-Paru Melalui Pengendalian Polusi Udara Dan Rokok - Abdul Rivai Saleh Dunggio; Yermi Yermi; Muh. Rudini; Nurhaedah Nurhaedah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Lung disease is a public health problem with a steadily increasing prevalence, primarily due to exposure to air pollution and smoking. Air pollution, both from outdoor and indoor environments, as well as active and passive cigarette smoke, are major risk factors for respiratory disorders. Low public knowledge and awareness of the dangers of air pollution and cigarettes contribute to the increasing number of lung diseases. This Community Service activity aims to improve public knowledge, attitudes, and awareness in efforts to prevent lung disease through education on air pollution control and smoking cessation. Implementation methods included health education, interactive discussions, demonstrations of clean and healthy living behaviors, and evaluation through pre- and post-tests. The results of the activity indicate an increase in public knowledge and awareness regarding the dangers of air pollution and cigarettes, as well as the importance of preventing lung disease. This education is expected to encourage behavioral changes in the community towards a healthier, smoke-free environment.